Identitas Kuliner Nusantara dalam Novel Namaku Alam karya Leila S. Chudori - Darmawan, Isnaini; Hartati, Dian; Sugiarti, Dewi Herlina; Nurfadilah, Kurnia Dewi (Lingua Susastra, 2025)
The popularity of foreign cuisine among Indonesia’s young generation has increased in line with the massive efforts of gastrodiplomacy, which has led to a decline in interest in Nusantara cuisine. The novel serves as a medium capable of creatively and symbolically exploring culinary themes. This study aims to analyze the representation of Nusantara culinary identity in Namaku Alam, a novel by Leila S. Chudori, through a literary gastrocriticism approach, focusing on the function of culinary elements as narrative devices, story settings, and the artistic values contained within. Data were collected through observation, documentation, and note-taking techniques on Namaku Alam. This study employs a descriptive qualitative method. The data, in the form of narrative excerpts containing culinary elements, were analyzed to interpret their symbolic and cultural meanings, thereby revealing the representation of Nusantara culinary identity in the text. The findings show that culinary elements in the novel function as a multifaceted narrative device that builds setting and plot while simultaneously constructing characters and triggering emotional conflict. Culinary aspects are also portrayed aesthetically through symbolic language that reflects the artistic value of origin, taste, presentation, and the manner of enjoying the food. This representation demonstrates that culinary elements in literary works are not merely decorative, but serve as an essential component in shaping the cultural identity of Nusantara.